Private Associations in the Ancient Greek World (Cambridge University Press, 2024)
Private associations abounded in the ancient Greek world and beyond, and this volume provides the first large-scale study of the strategies of governance which they employed. It explores them in their wider social, political, religious and global contexts and is valuable for historians, social scientists and theologians alike.